PERAN KEPOLISIAN DALAM MENANGANI KASUS TRADISI PENERBANGAN BALON UDARA DI PONOROGO - Zaid zaid; Ferdin Okta Wardana (Legalitas: Jurnal Hukum, 2021)
This study aims to reveal how the role of the police in handling the case of the traditional hot air balloon flight in Ponorogo which includes law enforcement, obstacles experienced, and future concepts based on the perspective of the police. Therefore, this research will be juridical and empirical by using a statutory and qualitative approach. After processing data using qualitative analysis, the results of this study reveal that the police have the authority to enforce the law against anyone who violates the order, safety, or laws and regulations. It's just that in matters of investigation, the police hand over the authority to the Civil Investigating Officer (PPNS) in the field of aviation. In addition, the police in each sector in Ponorogo Regency also have difficulties or obstacles, the majority of which are making tradition and lack of knowledge from the community and the lack of the role of local government as the main factors. Therefore, even the police, in this case, do not expect that this tradition should be eliminated, it's just that in the future there must be strict supervision and control so that the practice of this hot air balloon flight tradition does not endanger the safety and security of anyone and does not violate applicable laws.